2002
DOI: 10.1271/bbb.66.363
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent Products After Antioxidant Actions of β-Carotene and α-Tocopherol Have NoSalmonellaMutagenicity

Abstract: b-Carotene and a-tocopherol are important antioxidants biologically, but whether their oxidized products are toxic or not remains to be discovered. Here, we chromatographically separated 5 pure products or isomeric mixtures from reaction mixtures of b-carotene and reactive oxygens, and 17 lipid-radical scavenging products of a-tocopherol. The products were tested for mutagenicity using Salmonella typhimurium TA98, TA100, TA102, and TA104, in the presence and absence of S9. None showed mutagenicity against any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It should be noted that 1a and 2a, having no radical scavenging activity, act as antioxidants in the membrane system. Because the lipid peroxidation process is complicated by an initiation step characterized as hydrogen extraction by free radical species and a propagation step by a radical chain reaction, a variety of reactions other than proton donation, for example, stable adduct formation with a free radical, might be involved in the antioxidant action of flavanones (20). In addition, metal ion for the production of additional free radicals might be involved in our lipid peroxidation system.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that 1a and 2a, having no radical scavenging activity, act as antioxidants in the membrane system. Because the lipid peroxidation process is complicated by an initiation step characterized as hydrogen extraction by free radical species and a propagation step by a radical chain reaction, a variety of reactions other than proton donation, for example, stable adduct formation with a free radical, might be involved in the antioxidant action of flavanones (20). In addition, metal ion for the production of additional free radicals might be involved in our lipid peroxidation system.…”
Section: Resultsmentioning
confidence: 99%
“…From the chemical structures of the two transformation products, 2,2 0 -dihydroxy-4,4 0 ,5,5 0 -bis(methylenedioxy)biphenyl has potential as an antioxidant, and its conjugated quinoid theoretically having no antioxidative efficacy might exhibit antioxidative efficacy due to the easy reduction of conjugated quinoid. Sun et al (2002) isolated and identified seven transformation products (Figure 12) from β-carotene benzene solution at 37 C using 2,2 0 -azobis(2,4-dimethylvaleronitrile) as the alkylperoxyl radical generator: 12-formyl-11-nor-β,β-carotene (C1a), 15 0 -formyl-15-nor-β,β-carotene (C1b), 19-oxomethyl-10-nor-β,β-carotene (C2), 5,6epoxy-5,6-dihydro-β,β-carotene (C3a), 13,15 0 -epoxyvinyleno-13,15 0 -dihydro-14,15-dinor-β,β-carotene (C4a), 15 0 ,13epoxyvinyleno-13,15 0 -dihydro-14,15-dinor-β,β-carotene (C4b), and 11,15 0 -dihydrooxepin-β,β-carotene (C5). Subsequently, some other transformation products formed in different systems due to epoxidation, oxidation, isomerization, rearrangement, and decomposition were also identified such as 5,8-epoxy-β-carotene (C3b), 15,15 0 -epoxy-β-carotene (C3c), 5,6,5 0 ,6 0 -diepoxy-β-carotene (C6a), 5,8,5 0 ,8 0 -diepoxy-β-carotene (C6b), β-carotene-2,2 0 -ionone (C7), 6 0 -apo-β-carotenal (C8), 8 0 -apo-β-carotenal (C9), 10 0 -apo-β-carotenal (C10), 12 0 -apo-β-carotenal (C11), 14 0 -apo-β-carotenal (C12), 15-apo-β-carotenal (C13), 13-apo-β-carotenone (C14), 11-apo-β-carotenal (C15), 9-apo-β-carotenone (C16), β-cyclocitral (C17), 5,6-epoxy-β-ionone (C18a), 4-oxo-β-ionone (C18b), dihydroactinidiolide (C19), and 5,6-epoxy-8 0 -apo-β-carotenal (C20) (Figure 12).…”
Section: Loss Of Natural Antioxidants At Room Temperature Storagementioning
confidence: 99%
“…F I G U R E 1 2 Chemical structures of transformation products of β-carotene. Source: The figure has been adapted fromRibeiro et al, 2018;Rodriguez & Rodriguez-Amaya, 2007;Sun et al, 2002;Zeb & Murkovic, 2013 with permission from Elsevier and Oxford University Press.…”
mentioning
confidence: 99%